Database for accidents and incidents in the fuel ethanol industry - Calvo Olivares, Romina Daniela (2015)
The purpose of the present research is to collect information about accidents and incidents that have occurred at fuel ethanol facilities from 1998 to October 2014, and to keep complete unified records of them in a database. The developed database contains general information about the accident or incident, its sequence, mitigation measures, its causes and consequences for humans, environment and for the plant. Until now, this information is not available. The work consisted in gathering information from different documental sources and subsequent organization in a database. It complements the previous work made for biodiesel industry and fills the existing gap in the field of ethanol. Knowledge about this information enables us to manage plant risks, since the accidents that are more likely to occur and the main sources of risk can be easily identified. Also, it makes it possible to exchange information with interested third parties. Statistical analysis shows that accident frequency has an oscillatory behavior, rising in the last year. Fire is the most common type of accident, while equipment mechanical failure is the main cause of accident. Partial material loss has been identified as the most common consequence. Finally, some conclusions are obtained concerning to the importance of having an updated and complete accident and incident database.